2014
DOI: 10.1371/journal.ppat.1004537
|View full text |Cite
|
Sign up to set email alerts
|

Differential PfEMP1 Expression Is Associated with Cerebral Malaria Pathology

Abstract: Plasmodium falciparum is unique among human malarias in its ability to sequester in post-capillary venules of host organs. The main variant antigens implicated are the P. falciparum erythrocyte membrane protein 1 (PfEMP1), which can be divided into three major groups (A–C). Our study was a unique examination of sequestered populations of parasites for genetic background and expression of PfEMP1 groups. We collected post-mortem tissue from twenty paediatric hosts with pathologically different forms of cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…As DC8 CIDRα1.1 and group A CIDRα1.7 transcript levels were increased in peripheral blood of severe swelling and fatal cases (Figures 3B and 3C) we sought to connect these observations to our var typing of brains from autopsies of pediatric CM cases from 1999–2003 (Tembo et al, 2014). Most of the var sequences present in a patient can be captured by amplifying DBLα “tags” using degenerate primers targeting semi-conserved motifs in the N-terminal DBLα domain (Figure 5A)(Lavstsen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As DC8 CIDRα1.1 and group A CIDRα1.7 transcript levels were increased in peripheral blood of severe swelling and fatal cases (Figures 3B and 3C) we sought to connect these observations to our var typing of brains from autopsies of pediatric CM cases from 1999–2003 (Tembo et al, 2014). Most of the var sequences present in a patient can be captured by amplifying DBLα “tags” using degenerate primers targeting semi-conserved motifs in the N-terminal DBLα domain (Figure 5A)(Lavstsen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the var sequences present in a patient can be captured by amplifying DBLα “tags” using degenerate primers targeting semi-conserved motifs in the N-terminal DBLα domain (Figure 5A)(Lavstsen et al, 2012). We previously found two common DBLα tags amplified directly from brain tissue of fatal pediatric CM cases: var62B1-1 (5 of 20, 25% CM cases; GenBank: KC678109) and var28B1-1 (4 of 20, 20% of CM cases; GenBank: KC678110) (Tembo et al, 2014). Downstream sequencing revealed that var62B1-1 is a group A CIDRα1.7 domain followed by a predicted ICAM-1 binding motif (DBLα1.1-CIDRα1.7-DBLβ3) (Tembo et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the companion manuscript from Gillrie et al found that representative DC8 CIDRα1.1 and DC13 CIDRα1.4 domains differed in the ability to block APC generation and APC binding to primary endothelial cells, as well as to modulate thrombin-induced barrier dysfunction of endothelial cells, consistent with our findings here. Notably, in malaria autopsy studies, UpsB var transcripts were increased in cerebral vessels from CM1 cases and UpsA transcripts in CM2 cases (Tembo et al , 2014). The UpsB promoter is associated with CD36 binding parasites and the chimeric DC8 var gene (UpsB promoter and group A coding region), neither of which would be expected to have as potent APC blockade activity as the UpsA associated DC13 CIDRα1.4 domain.…”
Section: Discussionmentioning
confidence: 99%
“…For other complications, the association between particular var gene expression and pathology is less clear. A clinicopathological study performed on fatal pediatric patients in Malawi suggested that distinct var genes are dominantly expressed in the different organs of the same patients, although further conclusions are difficult in view of the technical limitations (Tembo et al 2014). Var genes containing domain cassettes 8 or 13 are preferentially upregulated in iRBCs that bind to primary microvascular ECs from brain, lungs and skin, are associated with severe malaria and are recognized by Abs from young African children from malaria-endemic regions Claessens et al 2012;Lavstsen et al 2012;Turner et al 2015).…”
Section: Excessive Irbc Sequestrationmentioning
confidence: 99%